2020
DOI: 10.1038/s41467-020-15020-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation of vocal and facial anatomy genes in modern humans

Abstract: Changes in potential regulatory elements are thought to be key drivers of phenotypic divergence. However, identifying changes to regulatory elements that underlie humanspecific traits has proven very challenging. Here, we use 63 reconstructed and experimentally measured DNA methylation maps of ancient and present-day humans, as well as of six chimpanzees, to detect differentially methylated regions that likely emerged in modern humans after the split from Neanderthals and Denisovans. We show that genes associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
117
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 82 publications
(132 reference statements)
10
117
1
Order By: Relevance
“…It is therefore tempting to speculate that some of this morphological divergence could be mediated by regulatory changes leading to minor differences in SOX9 expression levels during CNCC development. In fact, EC1.45, featured in this study, overlaps a Neanderthal-specific hypomethylated region from bone samples (based on reconstructed DNA methylation maps; Gokhman et al., 2014 , 2020 ; Figures 7 A, 7D, and S6 I). Although somewhat speculative, this suggests that the Neanderthal enhancer element might have retained regulatory activity longer during development (because DNA methylation is generally associated with silencing) compared with the human enhancer, which becomes decommissioned during chondrogenesis and is hypermethylated in human bones of various origins ( Figures 3 C–3E).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…It is therefore tempting to speculate that some of this morphological divergence could be mediated by regulatory changes leading to minor differences in SOX9 expression levels during CNCC development. In fact, EC1.45, featured in this study, overlaps a Neanderthal-specific hypomethylated region from bone samples (based on reconstructed DNA methylation maps; Gokhman et al., 2014 , 2020 ; Figures 7 A, 7D, and S6 I). Although somewhat speculative, this suggests that the Neanderthal enhancer element might have retained regulatory activity longer during development (because DNA methylation is generally associated with silencing) compared with the human enhancer, which becomes decommissioned during chondrogenesis and is hypermethylated in human bones of various origins ( Figures 3 C–3E).…”
Section: Discussionmentioning
confidence: 63%
“…A Neanderthal-specific significantly hypomethylated region was identified at genomic coordinates chr17:68668482-68674772 (hg19) from previously published datasets ( Gokhman et al., 2014 , 2020 ) that overlaps the EC1.45 enhancer cluster. A heatmap was generated representing DNA methylation at CpG dinucleotides spanning the DMR locus for one chimp (rib), seven anatomically modern humans (femur, crania, teeth), one Denisovan (finger) and two Neanderthal (femur and toe) bone samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As consequences of hypermethylation, the expression level of the expanded XYLT1 allele was found being severely reduced in BSS fibroblasts. Notably, XYLT1 is a gene related to vocal and facial anatomy and it has been recently demonstrated that changes in DNA methylation in this gene correlate with the evolution of vocal tract in humans [ 23 ]. Remarkably, most patients with BSS have variations in pitch and voice quality associated to mild or moderate cognition delay [ 22 ].…”
Section: Unstable Gc-rich Repeats In 5′ Regulatory Regionsmentioning
confidence: 99%
“…A broad body of evidence suggests that environmental and experiential factors can trigger cascades of epigenetic modification that in turn mediate downstream molecular and behavioral phenotypes. In this study, we focused on DNA methylation in rhesus macaque and human blood samples using the flexibility of Illumina DNA methylation arrays as a translational platform to investigate DNA methylation in both human and non-human primate species [42][43][44][45] . In fact, we were able to identify Moreover, a DMR in PM20D1 similar to our results was recently identified in human blood samples in a longitudinal study of post-traumatic stress disorder 48 , and CAMK2A is one of the most well-understood genes mediating synaptic plasticity underlying fear learning in a variety of paradigms 49 .…”
Section: Discussionmentioning
confidence: 99%